High technology trade and the roles of absorptive capabilities in Malaysia - Fong, Leonard Litt Lam; Siong, Hook Law; Azman-Saini, W. N. W.; Ismail, Normaz Wana (SAGE Publications, 2023)
This article analyses the importance of high-technology trade as a channel of economic growth to ease Malaysia out of the middle-income trap. This study also wonders upon the missing absorptive capabilities that validate the likelihoods of dismal gross domestic product (GDP) growth since the 1990s. Using the autoregressive distributed lag (ARDL) approach and fully modified ordinary least squares (FMOLS) estimator as robustness checks, this study identifies the determinants of high-technology trade and the appropriate absorptive capability in enhancing economic growth. The empirical results from quarterly data from 1990 to 2015 proved that foreign direct investment, financial development and infrastructure are vital to develop a successful high-technology trade. Another important finding is that it validates the presence of trade openness (as absorptive capability) in order to magnify the benefits of research and development (R&D). This explains why, despite spending on R&D, these spending do not project to economic growth.